Environmental Impact Assessment of Heat and Power Cogeneration in Tehran Wastewater Treatment Plant Based on the Life Cycle Assessment - Mohammad Rahmati; Majid Rasouli; Hossein Haji Agha Alizadeh; Behnam Ataeiyan (Journal of Engineering)
One of the well-known methods for correctly managing sludge disposal is using produced sludges as fuel in biogas-burning power plants. This study employed the ReCiPe2016 life cycle assessment methodology in conjunction with SimaPro software to assess the environmental impacts of a biogas-fired power plant in Tehran with a total capacity of 2.4 MW. The results were analyzed, and the 13 necessary pieces of information for the biogas burning system per 1 MWh produced heat and power by the combined heat and power unit were considered. In anaerobic digestion, heat and power in all classes had reducing effects on the environment. The heat and power classes, reinforced steel, chrome steel, low alloy steel, copper, and cast iron, exhibited the highest environmental impacts within the integrated heat and power system. Among all impact classes, power (for anaerobic digestion) in the class of carcinogenic toxicity in humans with a value of −6.01976 kg 1,4-DCB and copper (for combined heat and power) in the marine environmental toxicity class with a value of 0.731434 kg 1,4-DCB had the most reduction effect and the most impact of pollutant on the environment among the considered classes, respectively. Conclusively, in the anaerobic digestion process, heat and power had a positive effect on the environment in all impact classes. So, sludge can be an adequate candidate and anaerobic digestion can be an eco-friendly method for power generation. Other effect classes are presented in detail as results. This study could guide the development of similar facilities globally, considering factors like wastewater volume and combined heat and power technology.